Trajectory of Corruption in the Implementation of Post-Reform Regional Autonomy - I Made Arie Widyasthana Wartana, Putra; Yufensia, Jeflin (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2025)
This article aims to elaborate on the relationship between corruption cases and decentralization policies in Indonesia. The decentralization policy is believed to be one of the sources of problems for the proliferation of corruption cases in Indonesia. Several previous research results show that more and more corruption cases occurred after the implementation of decentralization. The method used is a qualitative method with a literature study approach. The data collection technique was carried out by collecting various existing references that discussed issues of corruption and decentralization. Next, the data is analyzed to obtain a conclusion. This study is descriptive in nature because it focuses on describing corruption incidents that occurred in Indonesia after the enactment of the law on regional autonomy. The results of this research state that corruption is linked to decentralization because regions have the authority to manage their finances independently. Delegating authority to regions to manage their own finances has actually become a breeding ground for corruption. Apart from that, decentralization is also used by local governments as an arena for reaping profits and enriching themselves and their groups. Political dowries in every election/pilkada event also often become grounds for the growth of corruption cases in the decentralization era.